Protocol to Identify Unknown Flanking DNA Using Partially Overlapping Primer-based PCR for Genome Walking - Mengya Jia; Dongqin Ding; Xiaohua Liu; Haixing Li (Bio-Protocol)
Genome walking is a popular molecular technique for accessing unknown flanking DNAs, which has been widely used in biology-related fields. Herein, a simple but accurate genome-walking protocol named partially overlapping primer (POP)-based PCR (POP-PCR) is described. This protocol exploits a POP set of three POPs to mediate genome walking. The three POPs have a 10 nt 3' overlap and 15 nt heterologous 5' regions. Therefore, a POP can partially anneal to the previous POP site only at a relatively low temperature (approximately 50 °C). In primary POP-PCR, the low-temperature (25 °C) cycle allows the primary POP to partially anneal to site(s) of an unknown flank and many sites of the genome, synthesizing many single-stranded DNAs. In the subsequent high-temperature (65 °C) cycle, the target single-stranded DNA is converted into double-stranded DNA by the sequence-specific primer, attributed to the presence of this primer complement, while non-target single-stranded DNA cannot become double-stranded because it lacks a binding site for both primers. As a result, only the target DNA is amplified in the remaining 65 °C cycles. In secondary or tertiary POP-PCR, the 50 °C cycle directs the POP to the previous POP site and synthesizes many single-stranded DNAs. However, as in the primary PCR, only the target DNA can be amplified in the subsequent 65 °C cycles. This POP-PCR protocol has many potential applications, such as screening microbes, identifying transgenic sites, or mining new genetic resources.